The Influence Of Advertisement Appeal, Product Quality, And Brand Equity On Head & Shoulders Shampoo Purchase Decision In Surabaya - Herninda Dara Puspita Ayu; Nurhadi Nurhadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Purchasing decisions play an important role for companies as they impact profitability and business sustainability. This research aims to identify the influence of advertising appeal, product quality, and brand equity on the purchase decisions of Head & Shoulders shampoo products in Surabaya. The population of this study consists of Head & Shoulders shampoo users who have also watched the "Joe Taslim x Fadil Jaidi - Who Will Be the Next BA Head & Shoulders?" advertisement and are aged between 15 and 64 in Surabaya. The research sample consists of 155 respondents selected using purposive sampling technique. Quantitative data presentation technique was employed. The research analysis uses multiple regression analysis. The research results show that advertising appeal, product quality, and brand equity have a significant effect on purchasing decisions of Head & Shoulders shampoo in Surabaya.